2017
DOI: 10.3892/etm.2017.4736
|View full text |Cite
|
Sign up to set email alerts
|

Radioresistance of chordoma cells is associated with the ATM/ATR pathway, in which RAD51 serves as an important downstream effector

Abstract: Surgery followed by radiotherapy is the standard treatment for chordomas, which are a rare but low-grade type of bone cancer arising from remnants of the embryonic notochord. However, disease recurrence following radiotherapy is common, most likely due to endogenous DNA repair mechanisms that promote cell survival upon radiation strikes. The ataxia telangiectasia mutated/ataxia telangiectasia mutated and Rad3 related (ATM/ATR)-mediated pathway has a critical role in DNA repair mechanisms; however, it has rarel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 20 publications
1
5
0
2
Order By: Relevance
“…We thus speculate that the quiescent and low dividing subclones must be at the origin of radioresistance in this cell line. Confirming this hypothesis, the second study evaluated the response of the U-CH1 cell line to ionizing radiation and found the same rate of survival at 2Gy of X-rays as ours [41]. The variable degrees of radioresistance found can also be explained by the differences in proliferation, composition of extracellular matrix, and hypoxia.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…We thus speculate that the quiescent and low dividing subclones must be at the origin of radioresistance in this cell line. Confirming this hypothesis, the second study evaluated the response of the U-CH1 cell line to ionizing radiation and found the same rate of survival at 2Gy of X-rays as ours [41]. The variable degrees of radioresistance found can also be explained by the differences in proliferation, composition of extracellular matrix, and hypoxia.…”
Section: Discussionsupporting
confidence: 74%
“…Such an effect has never been obtained in vitro in chordoma, making ALDH a promising target for future preclinical experiments. Interestingly, the inhibition of RAD51 has been shown to sensitize chordoma cells to radiations in vitro [ 41 ]. Moreover, this inhibition also sensitizes cells to aldehyde treatment, substrates of ALDH activity [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…ATM overexpression has been correlated with poor response to radiotherapy and worse overall survival in rectal cancer and advanced nasopharyngeal carcinoma patients (Ho et al, 2016;Ko et al, 2016). High ATM protein levels have been associated with radioresistance in primary glioma, chordoma, and breast cancer cells (Tribius et al, 2001;Yin and Glass, 2011;Zhang et al, 2017). Fraser et al found that somatic ATM mutations are associated with poor prognosis in localized prostate cancer (Fraser et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Допускается, что радиорезистентность хордомы связана с эндогенными механизмами репарации ДНК, которые способствуют выживанию клеток при лучевой нагрузке [29]. Эти механизмы обеспечиваются, в частности, серин/треониновой киназой и белком RAD51.…”
Section: особенности лечения хордомunclassified
“…Эти механизмы обеспечиваются, в частности, серин/треониновой киназой и белком RAD51. В ткани хордомы, в сравнении с окружающей здоровой тканью, уровень RAD51 значительно выше [29]. Путем гомологичной рекомбинации RAD51 восстанавливает разрыв, используя в качестве образца похожую или идентичную молекулу ДНК.…”
Section: особенности лечения хордомunclassified